Transitional care for rheumatic conditions in Europe: current clinical practice and available resources - Daniel Clemente; Leticia Leon; Helen Foster; Loreto Carmona; Kirsten Minden (BMC, 2017)
Abstract Objective To assess European pediatric rheumatology providers' current clinical practices and resources used in the transition from child-centered to adult-oriented care. Methods European pediatric rheumatologists were invited to complete a 17-item anonymized e-survey assessing current transition practices, transition policy awareness, and needs in advance of the publication of EULAR/PReS recommendations on transition. Results The response rate was 121/276 (44%), including responses from 115 centers in 22 European Union countries. Although 32/121 (26%) responded that their centers did not offer transition services, the majority (99%) agreed that a formalized process in transitioning patients to adult care is necessary. A minority (<30%) of respondents stated that they have a written transition policy although 46% have an informal transition process. Designated staff to support transitional care were available in a minority of centers: nurse (35%), physiotherapist (15%), psychologist (15%), social worker (8%), and occupational therapist (2%). The existence of a designated team member to coordinate transition was acknowledged in many centers (64% of respondents) although just 36% use a checklist for young people as part of individualized transitional care. Conclusion This survey of European pediatric rheumatology providers regarding transitional care practices demonstrates agreement that transitional care is important, and wide variation in current provision of transition services exists.